Effect of substrate concentration in producing higher butanol compared to ethanol by using clostridium acetobutylicum - Kartar Singh, Pearljeet Kaur (2010)
In this present experiment, the main objective is to study the effect of substrate concentration in producing higher butanol compared to ethanol by using Clostridium acetobutylicum. Palm oil mill effluent (POME) was used as the main substrate in this fermentation because it imposes negative effect towards the environment which in vast amount besides the availability as a low cost substrate and reinforced clostridium medium (RCM) was used as a control substrate. Study was also done to investigate the growth profile of C. acetobutylicum, type of sugars in POME, and glucose consumption of C. acetobutylicum during fermentation. The HPLC analysis result for sugar component showed that the reducing sugars; fructose, glucose, galactose, sucrose and lactose exist in POME and are utilized as substrate for solvents fermentation by C. acetobutylicum. Main study on the effect of four substrate concentrations 70%, 80%, 90% and 100% in POME and RCM were tested using Schott bottle as fermentor in anaerobic chamber to maintain the anaerobic condition for C. acetobutylicum growth condition for 72 hours at temperature of 35oC, pH 5.8 and speed of 200 rpm. The results showed that butanol and ethanol were produced at the end of the fermentation hence proving POME is a viable substrate for the fermentation. After 20 hours fermentation it was observed that at 90% substrate concentration butanol produced was higher compared to ethanol. However, in overall the result showed higher ethanol production compared to butanol production for all the four different substrate concentration throughout the experiment. The core factor contributing in this result is the substrate inhibition by butanol besides the phenolic component in POME which also acts as inhibitor, strain degeneration, and also extraction of butanol from fermentation broth. In conclusion, many efforts need to be taken to ensure higher butanol can be produced especially in decreasing the inhibition factor towards butanol.